"Dear IOC": Considerations for the Governance, Valuation, and Evaluation of Trends and Developments in eSports - Dees B. W. Postma; Robby W. van Delden; Ivo M. van Hilvoorde; Ivo M. van Hilvoorde (Frontiers Media S.A., 2022)
In 2021, the International Olympic Committee ventured virtual space by launching their first ever Olympic Virtual Series - featuring virtual baseball, cycling, rowing, sailing and motor racing. Interestingly, all these virtual events take strongly after their physical counterparts. Which begs the question: Where are the massively popular esports games like Fortnite, League of Legends, and Dota?-What do the Olympic Virtual Series have that these popular video games do not? Here, we argue for the inclusion of esports within the Olympic program. In many respects, esports "act" and "behave" just like traditional sports. We argue that esports and traditional sports share many of the same values, like the values of meritocracy, competition, fair play, and the value of having a "level playing field". Yet, in esports, many of these values remain underappreciated, losing out to negative values such as physical inactivity and game-addiction. To preserve what is worth preserving, we borrow from Value Sensitive Design to ameliorate the design-tensions that are foregrounded in esports. Thereby, paving possible ways toward the inclusion of esports in the Olympic program. Ultimately, the question for the IOC should not be "does it look like 'real sport', as we know it?", but rather: are they sporting, rule-led, and fair activities worth preserving and setting an example for a new digitally savvy generation?